Anglo-American Strategic Relations and the Far East 1933-1939. - Kennedy, Greg (Cass series--strategy and history., 2013)
This volume charts how the national strategic needs of the United States of America and Great Britain created a ""parallel but not joint"" relationship towards the Far East as the crisis in that region evolved from 1933-39. In short, it is a look at the relationship shared between the two nations with respect to accommodating one another on certain strategic and diplomatic issues so that they could become more confident of one another in any potential showdowns with Japan.